Institutional investors and corporate investment - Cristina Cella (Sveriges Riksbank, 2019)
Using investors' trading horizons to capture their incentives to collect information and monitor management's decisions, this paper shows that an increase in the ownership stake held by long-term institutional investors is associated with a subsequent decrease in real investment precisely in firms that invest too much. In support of the monitoring hypothesis, we show that results are driven by the purchases of long-term investors, while quasi-indexers and short-term investors have no influence on investment. We address the potential problem of endogeneity using the inclusion of a firm to the S&P 500 Index as an exogenous shock to institutional holdings.
Keywords: B2; G31; G32; 330; Institutional ownership; investors' investment horizons; over-investment; under-investment; management monitoring